Azerbaijani pseudoscientific theses and propaganda tools about anti-Semitism in Armenia - Teteyan, Arshaluys (History and Culture, 2025)
In the context of modern geopolitical events, an important place is occupied by the study and analysis of false theories and theses about anti-Semitism in Armenia, which are disseminated by Azerbaijani scientific, social and political circles. This article presents the inconsistency of Azerbaijani propaganda theses disseminated by foreign, including Jewish experts, analysts, whose goal is to create a negative opinion about Armenia in the current geopolitical stage, disseminating false information about the intolerance of the Armenian people. The purpose of this propaganda is to divert the attention of the international community from the genocidal actions of the Azerbaijani side during the 44-day Artsakh War and in subsequent years. All these theses are baseless and have no sources or factual basis. This article, based on an analysis of factual material, presents the support of the Armenian communities for the Resistance movement in various European countries and numerous cases of rescue of Jews. The Jewish community of Armenia has been mentioned since ancient times. The situation and activities of Jews in Armenia during the period of the Russian Empire and later in the Soviet Union are also presented, which once again proves the inconsistency of attempts to create contradictions between the two peoples and accusations of anti-Semitism in Armenia.
Keywords: Anti-Semitism; Azerbaijani falsification; Jewish community; Resistance Movement; Righteous Among the Nations; World War II; Manouchian Group